2009
DOI: 10.1016/j.jtcvs.2008.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio and its association with survival after complete resection in non–small cell lung cancer

Abstract: Increasing preoperative neutrophil/lymphocyte ratios are associated with higher stage but remain an independent predictor of survival after complete resection for primary lung cancer and are a potential biomarker to stratify high risk of death in patients with stage I disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
420
3
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(452 citation statements)
references
References 12 publications
(12 reference statements)
23
420
3
6
Order By: Relevance
“…Patients with colorectal, ovary and lung cancer were preoperatively stratified according to NLR as those with NLR>5 and those with NLR<5. It was reported that cancer-related mortality was significantly higher in patients with NLR>5 (Sarraf et al, 2009;Chua et al, 2011). In a study on patients with colorectal cancer, Kishi et al reported that mortality was higher in patients with high NLR who had liver metastasis and received neo-adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with colorectal, ovary and lung cancer were preoperatively stratified according to NLR as those with NLR>5 and those with NLR<5. It was reported that cancer-related mortality was significantly higher in patients with NLR>5 (Sarraf et al, 2009;Chua et al, 2011). In a study on patients with colorectal cancer, Kishi et al reported that mortality was higher in patients with high NLR who had liver metastasis and received neo-adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR dropped after surgery, but upon relapse it rose again [382]. Similarly, Sarraf et al [154] observed higher NLR in more advanced non-small cell lung cancer patients and Fossatti et al [207] observed a marked and significant correlation between tumor grade of glioma patients and the extent of neutrophil infiltration as determined by the number of CD15 + MPO + cells [207]. In low grade tumors 40-50 % show neutrophil infiltration, while in glioblastoma multiforme over 85 % of the samples show neutrophil infiltration [207].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…Several recent studies have revealed a correlation between clinical outcomes with common solid tumors (colorectal cancer, lung cancer, breast cancer and pancreatic cancer, etc) and systemic inflammatory response, including plasma C-reactive protein (CRP), hypoalbuminemia, and a selective combination of C-reactive protein and albumin termed as Glasgow Prognostic Score (GPS) (Leitch et al, 2007;Hwang et al, 2011;Jiang et al, 2012;Fox et al, 2013;McMillan, 2013). There were also many studies reporting that haematological markers of systemic inflammatory response such as white blood cell count or its components (neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR)), platelet, and platelet-lymphocyte ratio (PLR) are also prognostic indicators for cancer clinical outcomes (Yamanaka et al, 2007;Cho et al, 2009;Kishi et al, 2009;Sarraf et al, 2009;Kwon et al, 2012;Dalpiaz et al, 2013;Fox et al, 2013). In addition, other inflammatory factor combinations such as Prognostic Index (PI) and Prognostic Nutritional Index (PNI) have also been linked with prognosis of malignancies (Kasymjanova et al, 2010;Nozoe et al, 2010;Kanda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%